Caroline Ritter (2021) - Imperial Encore. The Cultural Project of the Late British Empire - Leyris, Thomas (Revue d’histoire contemporaine de l’Afrique, 2024)
Recensé : Caroline Ritter, Imperial Encore. The Cultural Project of the Late British Empire, Oakland (CA), University of California Press, 2021, 253 p.